Development and implementation of two-stage boost converter for single-phase inverter without transformer for PV systems - Basem E. Elnaghi; Mohamed E. Dessouki; M. N. Abd-Alwahab; Elwy E. Elkholy (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper offers a two-stage boost converter for a single-phase inverter without transformer for PV systems. Each stage of the converter is separately controlled by a pulse width modulated signal. A Simulink model of the converter using efficient voltage control topology is developed. The proposed circuit performance characteristics are explained and the obtained simulation results are confirmed through the applied experiments. Moreover, this paper has examined the control circuit of a single-phase inverter that delivers a pure sine wave with an output voltage that has the identical value and frequency as a grid voltage. A microcontroller supported an innovative technology is utilized to come up with a sine wave with fewer harmonics, much less price and an easier outline. A sinusoidal pulse width modulation (SPWM) technique is used by a microcontroller. The developed inverter integrated with the two-stage boost converter has improved the output waveform quality and controlled the dead time as it decreased to 63 µs compared to 180 µs in conventional methods. The system design is reproduced in Proteus and PSIM Software to analyze its operation principle that is confirmed practically.